"No Posttraumatic Stress Disorder in Lithuania": National Health Care Fails to Identify PTSD. Issue 1 (10th January 2017) - Kazlauskas, Evaldas; Zelviene, Paulina; Eimontas, Jonas
Abstract : Lithuanian National Health Insurance (NHI) registry data from 2014 and 2015 were used to estimate the annual rates of posttraumatic stress disorder (PTSD) and other stress‐related disorders in Lithuania. A large gap was found between 12‐month PTSD prevalence based on epidemiological data and annual PTSD rates based on health care service utilization in Lithuania. Estimations from the health care service's utilization data revealed that only about 0.01% to 0.02% of the population in Lithuania is diagnosed with PTSD annually, indicating that the national health care system identifies only about 1% of potential PTSD cases in Lithuania. The low rates of PTSD diagnoses in the health care system seem to indicate a lack of recognition of psychological trauma among general practitioners and mental health professionals in Lithuania. The lack of visibility of PTSD in the national health care system could be a major barrier to the treatment of PTSD in the country. The study indicates the importance of social factors, especially the recognition of trauma and PTSD, among health care professionals.